Тенденції розвитку хорової мініатюри у творчості Володимира Зубицького - Охманюк, Віталій Федорович; Okhmaniuk, Vitalii F. (Рівненський державний гуманітарний університет, 2017)
Проаналізовано значущість української хорової музики сучасного композитора В. Зубицького, окреслено здобутки композитора у розвитку хорової мініатюри. Дослідження проводилося на основі співставлення принципів роботи з фольклорним матеріалом В. Зубицького і творчого методу засновників жанру хорової обробки – М. Лисенка, К. Стеценка, М. Леонтовича. В результаті аналізу фольклорних мініатюр В. Зубицького визначені основні принципи побудови мініатюри фольклорного типу, виявлені їх органічний взаємозв’язок із традиціями української народнопісенної культури та подібність до принципів роботи з фольклорним матеріалом, віднайдених і запропонованих засновниками даного жанру.

The aim of the article is to analyze the significance of Ukrainian choral music by contemporary composer Volodymyr Zubytsky, in particular to outline his main achievements in the development of choral miniatures, namely the updating of the choral language by contemporary means of composer’s writing. The methodological basis of the research was work M. Varakuta, M. Dmytrenko, M.Zakovych, I. Ziaziun, O. Semashko. Results. Volodymyr Zubytsky chorus miniatures is a vivid example of a contemporary composer’s appeal to the traditional genre layers of national culture that have passed the centuries-old historical path and have become a kind of «business card» of the works of Ukrainian composers of previous generations Novelty. Is that the analysis, the significance of Ukrainian choral music by contemporary composer Volodymyr Zubytsky has been revealed, in particular, his main achievements in the development of choral miniatures, namely the updating of the choral language by contemporary means of composer’s writing, are outlined. The style of chorus miniatures by V. Zubytsky crystallized under the influence of the traditions laid down by M. Lysenko, K. Stetsenko, M. Leontovich, which was to the greatest extent found in choral miniatures of folk type. At the same time, stylistic tendencies, formed by V. Zubytsky in folklore miniature, have become an organic embodiment in the musical language of spiritual and secular miniatures. The practical significance of this study is that the results can be used to design training courses – study of art, cultural orientation, in the preparation of appropriate textbooks for art schools of different levels of accreditation.
Main trends of development of choir miniature in the context of Volodymyr Zubytsky
Keywords: Хорова мініатюра; народні мелодії; пісенний фольклор; композиторська діяльність; choir miniature; song folklore; folk melodies; composer’s activity